2019
DOI: 10.1111/ajag.12654
|View full text |Cite
|
Sign up to set email alerts
|

Dementia as a source of social disadvantage and exclusion

Abstract: Objective: To explore perceptions of the impacts of dementia on people living with the condition and those close to them and examine the relationship between dementia, disadvantage and social exclusion. Methods: Semi-structured in-depth interviews were conducted with 111 participants: people with dementia (n = 19), carers (n = 28), health-care professionals (n = 21), social workers (n = 23) and service professionals (n = 20). NVivo 11 was used to code descriptions and identify impact areas. Results: Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…Social function may deteriorate due to conversion to dementia; however, the limitation and decrease of social activities may adversely affect the progression of dementia. This has been reported consistently in various studies [14-16, 22, 45-48]. Recently, a meta-analysis [49] concluded that social relationship factors that represent a lack of social interaction are associated with incident dementia.…”
Section: Discussionmentioning
confidence: 63%
“…Social function may deteriorate due to conversion to dementia; however, the limitation and decrease of social activities may adversely affect the progression of dementia. This has been reported consistently in various studies [14-16, 22, 45-48]. Recently, a meta-analysis [49] concluded that social relationship factors that represent a lack of social interaction are associated with incident dementia.…”
Section: Discussionmentioning
confidence: 63%
“…People with dementia face many challenges in maintaining their involvement in the community; for example, their memory difficulties can make it difficult for them to go shopping or use public transport (Alzheimer's Society, 2013). People with dementia may have restricted opportunities for social participation, leading to a loss of social connection in their community (Biggs et al, 2019). Dementia also has an impact on a person's confidence; underlying worries and fears may prevent people from engaging in activities (ADI, 2019;Alzheimer's Society, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further searches were conducted within these results using the additional search terms "caregiver," "caregiver burden," "stress," "behavioral and psychological symptoms of dementia," "BPSD," "economic," "financial," "autonomy," "dignity," "identity," "personhood" and "ethics." By this method, a total of 103 citations were retained (Pereira, 2011;Schuurmans et al, 2021;Kemmelmeier et al, 2002;Bradley, 2009;Baeke et al, 2011;Chakraborty et al, 2017;Madadin et al, 2020;Nichols, 2013;Emanuel et al, 2000;Krag, 2014;Trachtenberg and Manns, 2017;Bilchik, 1996;Lazar and Davenport, 2018;Karrer et al, 2020;StakiĆĄaitis et al, 2019;Finucane et al, 2007;Finucane, 1999;Sachs et al, 2004;Dominguez et al, 2021;Meier, 1997;Liu et al, 2020;Gao et al, 2019;Gilhooly et al, 2016;Watson et al, 2019;Cheng, 2017;Biggs et al, 2019;Fam et al, 2019;Dening et al, 2013;Owen et al, 2001;Cohen-Mansfield and Brill, 2020;Anderson et al, 2019;O'Dwyer et al, 2016;Bravo et al, 2018;Wicher and Meeker, 2012;Stolz et al, 2015;Seike et al, 2021;Kashimura et al, 2021;Zwingmann et al, 2018;…”
Section: Pitfalls Inherent In the Practice Of Pas In The Specific Case Of Dementiamentioning
confidence: 99%